2018
DOI: 10.1016/j.molcel.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Global Maps of ProQ Binding In Vivo Reveal Target Recognition via RNA Structure and Stability Control at mRNA 3′ Ends

Abstract: The conserved RNA-binding protein ProQ has emerged as the centerpiece of a previously unknown third large network of post-transcriptional control in enterobacteria. Here, we have used in vivo UV crosslinking and RNA sequencing (CLIP-seq) to map hundreds of ProQ binding sites in Salmonella enterica and Escherichia coli. Our analysis of these binding sites, many of which are conserved, suggests that ProQ recognizes its cellular targets through RNA structural motifs found in small RNAs (sRNAs) and at the 3' end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
267
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(288 citation statements)
references
References 88 publications
19
267
0
2
Order By: Relevance
“…We wondered whether the ProQ-cspE B3H interaction might be limited by competition with endogenous ProQ or cellular Hfq, given that co-immunoprecipitation studies have suggested that ProQ and Hfq may compete for a subset of their RNA substrates. (22,37) While no additional stimulation of transcription over basal levels was observed when the ProQ-cspE B3H experiment was repeated in ΔproQ reporter cells ( Fig 1C; 1.2), we found that the fold-stimulation of β-gal transcription indeed increased in Δhfq reporter cells ( Fig 1D; 2.3x). This Δhfq reporter strain was previously used for detecting Hfq-RNA interactions, (30) and was used throughout the remainder of this study.…”
Section: Establishing a B3h Assay For Proq-rna Interactionsmentioning
confidence: 66%
See 3 more Smart Citations
“…We wondered whether the ProQ-cspE B3H interaction might be limited by competition with endogenous ProQ or cellular Hfq, given that co-immunoprecipitation studies have suggested that ProQ and Hfq may compete for a subset of their RNA substrates. (22,37) While no additional stimulation of transcription over basal levels was observed when the ProQ-cspE B3H experiment was repeated in ΔproQ reporter cells ( Fig 1C; 1.2), we found that the fold-stimulation of β-gal transcription indeed increased in Δhfq reporter cells ( Fig 1D; 2.3x). This Δhfq reporter strain was previously used for detecting Hfq-RNA interactions, (30) and was used throughout the remainder of this study.…”
Section: Establishing a B3h Assay For Proq-rna Interactionsmentioning
confidence: 66%
“…Residues 2-119, 2-131, 2-176, 181-232 and 2-232 of E. coli ProQ were fused to the ɑ-NTD (residues 1-248) in pBRɑ between NotI and BamHI to generate pSP90 (pBRɑ-ProQ NTD ), pKB951 (pBRɑ-ProQ NTD+12aa ), pKB955 (pBRɑ-ProQ ΔCTD ), pSP92 (pBRɑ-ProQ CTD ) and pKB949 (pBRɑ-ProQ FL , full-length) respectively. pCW17 (pAC-p constit -λCI-MS2 CP ) was derived from pKB989 (pAC-p lacUV5 -λCI-MS2 CP ) (22) by substitution of the region between -35 and +22 of the p lacUV5 promoter (containing the -35, -10 and lacO elements) with the following sequence lacking a lacO element (predicted -35, -10 and TSS of the resulting constitutive promoter are underlined):…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…For low aeration conditions, overnight NSLB cultures were subcultured 1/100 into 16 ml of HSLB in a 20 × 150 mm tube and incubated for 3 h on a platform shaker at 225 rpm. For the measurement of the half‐life of hilD mRNA, 500 μg of rifampicin was added into the bacterial cultures (Holmqvist et al , ). Immediately upon addition of rifampicin (time 0) and at 1, 2, 4, 8 and 16 min after the treatment, 800 μl aliquots of bacterial cells were collected.…”
Section: Methodsmentioning
confidence: 99%